Answer:
See proof below
Step-by-step explanation:
show that
sinx/1+cosx=tanx/2
From LHS
sinx/1+cosx
According to half angle
sinx = 2sinx/2 cosx/2
cosx = cos²x/2 - sin²x/2
cosx = cos²x/2 - (1- cos²x/2)
cosx = 2cos²x/2 - 1
cos x + 1 = 2cos²x/2
Substitute into the expression;
sinx/1+cosx
= (2sinx/2 cosx/2)/2cos²x/2
= sinx.2/cos x/2
Since tan x = sinx/cosx
Hence sinx/2/cos x/2 = tan x/2 (RHS)
This shows that sinx/1+cosx=tanx/2
According to the euclidean triangle theorem
9 = z² / 13
z² = 9 x 13 = 117
z = 3 √13
Answer:
Hii i just know the 4 and 5 one
Step-by-step explanation:
4 one is exterior
5 one is included angle
Step-by-step explanation:
number2 the answer is a and
number 3 the answer is letter b